2020
DOI: 10.1007/s10603-020-09468-8
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding National Preferences in EU Consumer Policy: A Regime Approach

Abstract: EU consumer policy is a policy area that is receiving increased attention and is considered important for the proper functioning of the internal market. Yet, as with many other supranational policy areas, conflicting positions of the Member States have led to many compromises and rejections of EU-initiated proposals. By building on regime theory and previous research identifying consumer policy regimes, the aim with this article is to investigate potential patterns in countries’ preferences in EU consumer poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…European Union activities and legislation are strong drivers of improving consumer conditions at national levels (Nessel, 2019 ). The enforcement of consumer rights, however, is primarily left to national authorities, with support from consumer organizations (Austgulen, 2020 ). At the country level, there are two main organizational consumer policy models: state-funded institutions and volunteer organizations financed by membership fees and other sources.…”
Section: Introductionmentioning
confidence: 99%
“…European Union activities and legislation are strong drivers of improving consumer conditions at national levels (Nessel, 2019 ). The enforcement of consumer rights, however, is primarily left to national authorities, with support from consumer organizations (Austgulen, 2020 ). At the country level, there are two main organizational consumer policy models: state-funded institutions and volunteer organizations financed by membership fees and other sources.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on a study, three, four, or five different consumer protection regimes can be identified in Europe. According to one classification, there has been a Nordic negotiation model (industry associations and individual companies negotiate directly with consumer associations for common policy goals), a protection model with France as an example (consumer associations and the state have had a strong influence upon policy goals), and an information model with Austria and Germany as examples (industry associations and the state have had a dominant role) [1]. In addition, it is possible to identify further models by casting the focus on the British-influenced administrative tradition as well as the eastern and southern member states.…”
Section: Administrationmentioning
confidence: 99%
“…A partial explanation originates from the domain; it is difficult to legislate consumer goods and services due to the pace of innovation and technological progress. But another partial explanation stems from different cultures and historical trajectories; the power struggles between the organized interests of consumers and producers affected regulatory traditions differently in different member states [1]. A similar struggle between organized interests has affected consumer law at the EU level [56].…”
Section: Introductionmentioning
confidence: 99%
“…tection regimes can be identified in Europe. According to one classification, there has been a Nordic negotiation model (industry associations and individual companies negotiate directly with consumer associations for common policy goals), a protection model with France as an example (consumer associations and the state have had a strong influence upon policy goals), and an information model with Austria and Germany as examples (industry associations and the state have had a dominant role) [1]. In addition, it is possible to identify further models by casting the focus on the British-influenced administrative tradition as well as the eastern and southern member states.…”
Section: Administrationmentioning
confidence: 99%
“…A partial explanation originates from the domain; it is difficult to legislate consumer goods and services due to the pace of innovation and technological progress. But another partial explanation stems from different cultures and historical trajectories; the power struggles between the organized interests of consumers and producers affected regulatory traditions differently in different member states [1]. A similar struggle between organized interests has affected consumer law at the EU-level [49].…”
Section: Introductionmentioning
confidence: 99%